1999
DOI: 10.1046/j.1570-7458.1999.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diuraphis noxia resistance in wheat isolines and plant introduction lines

Abstract: The Russian wheat aphid, Diuraphis noxia (Mordvilko), is one of the most important aphid pests of wheat, Triticum aestivum L., worldwide. Among the various pest management options, plant resistance is an economical management tactic to control D. noxia in cereal crops such as wheat. Researchers have identified D. noxia resistant germplasm and it has been incorporated into wheat. This study compared D. noxia resistance between the 'Betta' wheat isolines Betta-Dn1, Betta-Dn2, and Betta-Dn5 and their correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…2B). Budak et al (1999) observed similar results when compared the biomass of D. noxia collected from different ÔBettaÕ wheat lines with the same Dn genes. They concluded Betta-Dn5 did not show the same level of resistance to D. noxia as the donor line PI 294994 and suggested that resistance inherited from PI 294994 might be controlled by more than one gene.…”
Section: Discussionsupporting
confidence: 61%
“…2B). Budak et al (1999) observed similar results when compared the biomass of D. noxia collected from different ÔBettaÕ wheat lines with the same Dn genes. They concluded Betta-Dn5 did not show the same level of resistance to D. noxia as the donor line PI 294994 and suggested that resistance inherited from PI 294994 might be controlled by more than one gene.…”
Section: Discussionsupporting
confidence: 61%
“…Both aphid species were preconditioned following procedures by Budak et al (1999). To infest wheat plants, either 0 or 15 aphids were introduced onto the second fully expanded leaf blade by using a camelÕs-hair brush.…”
Section: Methodsmentioning
confidence: 99%
“…Interactions between Betta (susceptible parent) wheat (Du Toit 1988) and its two isogenic lines (Betta-Dn1, antibiosis and Betta-Dn2, tolerance) (Du Toit 1989, Budak et al 1999) challenged by two D. noxia densities (0 and 20 aphids) were evaluated in this study. Plants from each of the three wheat lines were infested with 20 D. noxia at 14 d after planting.…”
Section: Methodsmentioning
confidence: 99%